The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12864-018-4950-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis identifies the key genes involved in stamen petaloid in lotus (Nelumbo nucifera)

Abstract: BackgroundFlower morphology, a phenomenon regulated by a complex network, is one of the vital ornamental features in Nelumbo nucifera. Stamen petaloid is very prevalent in lotus flowers. However, the mechanism underlying this phenomenon is still obscure.ResultsHere, the comparative transcriptomic analysis was performed among petal, stamen petaloid and stamen through RNA-seq. Using pairwise comparison analysis, a large number of genes involved in hormonal signal transduction pathways and transcription factors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 56 publications
3
40
0
Order By: Relevance
“…It has been declared that stamen petaloid is more similar to petal than to stamen. This is consistent with stamen petaloid having the petal morphology as previously reported [15]. The number of DEGs between C vs Cp and P vs Cp did not show any significant difference, suggesting that the abnormal flower organ (carpel petaloid) remained more of the carpel trait with petal-like features.…”
Section: Overview Transcriptomic Datasupporting
confidence: 91%
See 4 more Smart Citations
“…It has been declared that stamen petaloid is more similar to petal than to stamen. This is consistent with stamen petaloid having the petal morphology as previously reported [15]. The number of DEGs between C vs Cp and P vs Cp did not show any significant difference, suggesting that the abnormal flower organ (carpel petaloid) remained more of the carpel trait with petal-like features.…”
Section: Overview Transcriptomic Datasupporting
confidence: 91%
“…These candidate genes were reported that they involved in stamen petaloid [15]. These indicate that GH3 and GATA are essential in petal formation and promote to alteration other floral organs to petal-like feature.…”
Section: Genes Associated With Petaloidmentioning
confidence: 81%
See 3 more Smart Citations